1998
DOI: 10.1128/jb.180.5.1342-1345.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutants Devoid of Neutral Trehalase Activity in the Fission Yeast Schizosaccharomyces pombe : Partial Protection from Heat Shock and High-Salt Stress

Abstract: Exposure of cells of Schizosaccharomyces pombe to heat shock or osmotic upshift results in an increased level of neutral trehalase activity, which is responsible for hydrolysis of intracellular trehalose. We constructed S. pombe mutants lacking neutral trehalase activity by gene replacement at the newly defined ntp1 + locus. Analysis of these mutants revealed that a twofold increase in trehalose accumulation, enhanced acquired thermoresistance, and marked salt tolerance characterized their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…In a previous work we described that ntp1-disrupted strains of S. pombe, which are devoid of neutral trehalase activity, were able to sporulate [12]. In the present study we analysed the germination of these spores in liquid medium and found marked di¡erences when compared to wild-type spores.…”
Section: Germination In Control and Ntp1-disrupted Sporessupporting
confidence: 47%
See 3 more Smart Citations
“…In a previous work we described that ntp1-disrupted strains of S. pombe, which are devoid of neutral trehalase activity, were able to sporulate [12]. In the present study we analysed the germination of these spores in liquid medium and found marked di¡erences when compared to wild-type spores.…”
Section: Germination In Control and Ntp1-disrupted Sporessupporting
confidence: 47%
“…Obviously, this can be explained by the occurrence in spores of other trehalase activity. The existence of additional neutral trehalase activity is di¤cult to rationalise since it escapes biochemical detection in ntp1-disrupted cells and no sig-ni¢cant homology was detected with other S. pombe genes during cloning of ntp1 as to suggest the existence of related enzymes [12]. Instead, a candidate enzyme to account for these results would be the sporulation-speci¢c acid trehalase described in spores and asci of the ¢ssion yeast [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicate that, in addition to the monomeric forms, at least two distinct complexes exist containing significant amounts of all three proteins. One corresponds to the high molecular mass complex (700-800 kDa) and the other to a more diffusely spread population corresponding to lower molecular mass range (80-250 kDa, fractions [12][13][14][15][16][17]. To clarify which of these protein complexes exhibit neutral trehalase activity, we prepared log-phase cultures from strain C335 and subjected them to thermal (40°C, 1 h) or osmotic (0.75 M NaCl, 2 h) stress.…”
Section: Analysis Of the Ntp1p-tps1p-tpp1p Complex By Hplc-gel Filtramentioning
confidence: 99%